2007
DOI: 10.1088/1367-2630/9/1/019
|View full text |Cite
|
Sign up to set email alerts
|

Effective-range description of a Bose gas under strong one- or two-dimensional confinement

Abstract: We point out that theories describing s-wave collisions of bosonic atoms confined in one-or two-dimensional geometries can be extended to much tighter confinements than previously thought. This is achieved by replacing the scattering length by an energy-dependent scattering length which was already introduced for the calculation of energy levels under 3D confinement. This replacement accurately predicts the position of confinementinduced resonances in strongly confined geometries.Many experiments investigating… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 34 publications
(90 reference statements)
3
75
1
Order By: Relevance
“….. Equation (46) permits to recover the results deduced by using the zero-range potential approach [18,[21][22][23].…”
Section: Quasi-2d Geometrymentioning
confidence: 98%
See 1 more Smart Citation
“….. Equation (46) permits to recover the results deduced by using the zero-range potential approach [18,[21][22][23].…”
Section: Quasi-2d Geometrymentioning
confidence: 98%
“…This issue has been already the subject to many theoretical studies [4,5,[18][19][20][21][22][23] where a zero-range potential approach was used and much more sophisticated multichannel studies have been performed in Refs. [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The difference was not ascribable to numerical imprecision, but rather because of the non-zero colliding energy. In a subsequent study [51], it has been showed that by using the formula (5) with the replacement a 3D → a 3D (k) in the so-called effective-range approximation [52,53] …”
Section: Atom-atom Confinement-induced Resonancesmentioning
confidence: 99%
“…A direct generalization of Olshanii's theory to anisotropic transverse confinement shows that there is only one harmonic CIR (HCIR) resonance, no matter how large the transverse anisotropy [19]. For large anisotropy, this theory crosses over smoothly to the case of a quasi-2D trap, where a single HCIR occurs with a negative S-wave scattering length, a 3D < 0 [20][21][22].…”
Section: Introductionmentioning
confidence: 98%